Data protection implementation guide a legal, risk and technology framework for the GDPR - Quinn, Brendan (Lawyer) (Kluwer Law International B.V., 2021)
The complexities of implementing the General Data Protection Regulation (GDPR) continue to grow as it progresses through new and ever-changing technologies, business models, codes of conduct, and decisions of the supervisory authorities, and the courts. This eminently practical guide to implementing the GDPR - written in an original, problem-solving style by a highly experienced data protection expert with equal knowledge of both law and technology - provides a step-by-step project management approach to building a GDPR-compliant data protection system, assessing, and documenting the risks and then implementing these changes through processes at the operational level. With detailed attention to case law (Member State, ECJ, and ECHR), especially where affecting high-risk areas that have attracted scrutiny, the guidance proceeds systematically through such topics and issues as the following: required documentation, policies, and procedures; risk assessment tools and analysis frameworks; children's data; employee and health data; international transfers post-Schrems II; data subject rights including the right of access; data retention and erasure; tracking and surveillance; and effects of technologies such as artificial intelligence, biometrics, and machine learning. With its practical examples derived from the author's experience in building GDPR-compliant software, as well as its analysis of case law and enforcement priorities, this incomparable guide enables company data protection officers and compliance staff to advise on key issues with full awareness of the legal and reputational risks and how to mitigate them. It is also sure to be of immeasurable value to concerned regulators and policymakers at all government levels.